Etude D’une Chaine de Conversion D’Energie Eolienne Modèle Et Simulation - Saif Eddine Djelali; Oualid Telaidjia (My University, 2023)
This thesis deals with the study of wind energy conversion systems using a double-fed asynchronous generator MADA. To achieve a thorough understanding of the proper functioning of the energy chain, we analyzed the results of different simulations under MATLAB. Through these simulations, we came to some insightful conclusions. Finally, we modeled the wind turbine in conjunction with the double-fed asynchronous generator and simulated the assembly using SIMULINK. ----------------------------------------------------------------------------------------------------------- الأعمال المنجزة في المذكرة تتعلق أساسا على النمذجة والمحاكاة لسلسلة توليد الكھرباء بالطاقة الھوائيةو التي تعتمدعلى مبدأ مولدة متزامنة من اجل استعمالھا في المناطق النائيةوكانت التحليلات لنتائج المحاكاة المختلفة في الماتلاب تعطي التصاریح التي تؤدي إلى استنتاجات مثيرة للاھتماملحسن سير العمل في سلسلة الطاقة. ولتأكيد النتائج المحصل عليھا باستعمال برنامج الماتلاب قمنا بإنشاء نموذج للنظام )توربينھوائي+مولد لاتزامني(باستعمال برنامج السيميلينك. ---------------------------------------------------------------------------------------------------------- Cette mémoire porte sur l'étude des systèmes de conversion d'énergie éolienne utilisant ungénérateur asynchrone à double alimentation MADA. Pour parvenir à une compréhension approfondie du bon fonctionnement de la chaîne énergétique, nous avons analysé les résultatsde différentes simulations sous MATLAB. Grâce à ces simulations, nous sommes arrivés àdesconclusions perspicaces. Enfin, nous avons modélisé l'éolienne en liaiso n avec le générateur asynchrone à double alimentation et simulé le montage sous SIMULINK.